CHARACTERIZING KAOLIN-BASED ADDITIVE FOR COMBUSTION OF SUGARCANE BAGASSE-DERIVED FUEL BY THERMAL ANALYSIS - Truong Giang, Nguyen; Xuan Quang, Mai (HNUE Journal of Science: Journal of Natural Sciences, 2024)
In this work, characterizing kaolin-based additive for combustion of sugarcane bagasse-derived biomass was investigated by TG-DTG and DTA. Sugarcane bagasse powder (SB) was mixed with kaolin powder (KL) at weight percentages of 0 wt.%, 2 wt.% and 4 wt.%, and then pressed into fuel pellets.   combustion parameters (ignition temperature Ti, burnout temperature Tb, maximum peak temperature Tmax, ignition index Ci, burnout index Cb, comprehensive combustibility index S and activation energy Ea) for the pellets were evaluated.